Spatio-temporal variabilities of soil phosphorus pool and phosphorus uptake with maize stover biochar amendment for 5 years of maize - Cao, Dianyun; Chen, Wenfu; Yang, Ping; Lan, Yu; Sun, Daquan (Environmental science and pollution research international, 2020)
Phosphorus reuse by application of biochar is a recent concept that needs to be supported by long-term field data. To monitor biochar's long-term effects on P turnover, one-off biochar was applied in 2013 with mineral NPK fertilizers being applied every year since then. Biochar application rates included 0 t ha-1 (CK), 15.75 t ha-1 (BC1), 31.5 t ha-1 (BC2), and 47.25 t ha-1 (BC3). Over the 5 years' field experiment, P distribution in soil profile, inorganic and organic P fractions in bulk, and rhizosphere soil and maize P uptake were determined. The results showed that biochar reduced the inorganic P fractions (Ca2-P, Ca8-P, Al-P, Fe-P and O-P by 4.8-33.7%, 8.8-59.0%, 13.7-28.6%, 8.4-17.6%, and 3.3-25.5%, respectively), and increased organic P fractions (MLOP and HROP by 67.2-11.6% and 18.8-87.7%, respectively) in bulk soil, while in rhizosphere soil, Fe-P and MLOP were decreased by 13.4-34.5% and 67.2-111.6%, respectively, in 2017. After the application of biochar for 5 years, moderately labile organic phosphorus (MLOP), moderately resistant organic phosphorus (MROP), and highly resistant organic phosphorus (HROP) with different biochar treatments were enhanced by 12.8-42.7%, 20.1-48.0%, and 5.5-66.6%, respectively, but Ca8-P, Al-P, O-P, and Ca10-P were all decreased by 18.6-24.9%, 16.4-21.4%, and 3.3-23.48%, respectively. Total P storage in 0-100 cm was declined by biochar. Increases in maize P uptake in the stover (38.6-71.3%) and grain (20.9-25.5%) were occurred after 31.5 t ha-1 and 47.25 t ha-1 biochar addition. To sum up, biochar is found to regulate the distribution, storage, and transformation of soil P, which lead to increase in maize P uptake.
Keywords: průmyslová hnojiva; Fertilizers; Soil; Charcoal; půda; kukuřice setá; Zea mays; dřevěné a živočišné uhlí; Phosphorus; fosfor